2014
DOI: 10.1371/journal.pone.0100436
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Swanson's Literature-Based Discovery: Anandamide Treatment Inhibits Growth of Gastric Cancer Cells In Vitro and In Silico

Abstract: Swanson's literature-based discovery focus on resurrecting previously published but neglected knowledge. In this study, we propose a two-step model of the discovery process and generate a hypothesis between anandamide and gastric cancer. Further, the potential relationship was confirmed by follow-up experimentation. The anandamide treatment resulted in cell cycle redistribution of gastric cancer cells. Most importantly, the variation of cell cycle was mediated by some genes from the B-terms of the closed disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Additionally, other data sources such as PubMed Central (PMC) Open Access (Ding et al, 2013), Science Direct (Vicente-Gomila, 2014), Web of Science (Sebastian, Siew & Orimaye, 2015), IEEE Xplore Digital Library (Qi & Ohsawa, 2016), Engineering Village (Kibwami & Tutesigensi, 2014), ProQuest (Kibwami & Tutesigensi, 2014), EBSCO Host (Kibwami & Tutesigensi, 2014), INSPEC (Ye, Leng & Guo, 2010) have also been employed by several other LBD approaches to retrieve the articles for analysis. (Dong et al, 2014), Gene Expression Omnibus (GEO) database (Hristovski et al, 2010), ArrayExpress (AE) database (Maver et al, 2013), Manually Annotated Target and Drug Online Resource (MATADOR) (Crichton et al, 2018), Biological General Repository for Interaction Datasets (BioGRID) (Crichton et al, 2018), PubTator (Crichton et al, 2018), Online Mendelian Inheritance in Man (OMIM) (Cohen et al, 2010) and TREC (Symonds, Bruza & Sitbon, 2014).…”
Section: What Are the Data Sources Used In Lbd Research?mentioning
confidence: 99%
“…Additionally, other data sources such as PubMed Central (PMC) Open Access (Ding et al, 2013), Science Direct (Vicente-Gomila, 2014), Web of Science (Sebastian, Siew & Orimaye, 2015), IEEE Xplore Digital Library (Qi & Ohsawa, 2016), Engineering Village (Kibwami & Tutesigensi, 2014), ProQuest (Kibwami & Tutesigensi, 2014), EBSCO Host (Kibwami & Tutesigensi, 2014), INSPEC (Ye, Leng & Guo, 2010) have also been employed by several other LBD approaches to retrieve the articles for analysis. (Dong et al, 2014), Gene Expression Omnibus (GEO) database (Hristovski et al, 2010), ArrayExpress (AE) database (Maver et al, 2013), Manually Annotated Target and Drug Online Resource (MATADOR) (Crichton et al, 2018), Biological General Repository for Interaction Datasets (BioGRID) (Crichton et al, 2018), PubTator (Crichton et al, 2018), Online Mendelian Inheritance in Man (OMIM) (Cohen et al, 2010) and TREC (Symonds, Bruza & Sitbon, 2014).…”
Section: What Are the Data Sources Used In Lbd Research?mentioning
confidence: 99%
“…Together with the reduction of estrogens, in postmenopausal women it has been also seen a decrease in AEA concentrations, similar to the luteal phase of premenopausal subjects [107]. Several authors reported the anti-cancer role of AEA, describing its capabilities to affect cell cycle distribution of gastric cancer cells [15,108,109] and also to reduce proliferation of neuroblastoma, prostate carcinoma and melanoma cells [110][111][112]. Cancer cells are more sensitive to endocannabinoids compared to healthy cells, since a most abundant presence of EC receptors on their surface [113].…”
Section: Role Of Endocannabinoids Systemmentioning
confidence: 90%
“…Additionally, other data sources such as PubMed Central (PMC) Open Access (Ding et al, 2013), Science Direct (Vicente-Gomila, 2014), Web of Science (Sebastian et al, 2015), IEEE Xplore Digital Library (Qi and Ohsawa, 2016), Engineering Village (Kibwami and Tutesigensi, 2014), ProQuest (Kibwami and Tutesigensi, 2014), EBSCO Host (Kibwami and Tutesigensi, 2014), INSPEC (Ye et al, 2010) have also been employed by several other LBD approaches to retrieve the articles for analysis. (Dong et al, 2014), Gene Expression Omnibus (GEO) database (Hristovski et al, 2010), ArrayExpress (AE) database (Maver et al, 2013), Manually Annotated Target and Drug Online Resource (MATADOR) (Crichton et al, 2018), Biological General Repository for Interaction Datasets (BioGRID) (Crichton et al, 2018), PubTator (Crichton et al, 2018), Online Mendelian Inheritance in Man (OMIM) (Cohen et al, 2010) and TREC (Symonds et al, 2014).…”
Section: What Are the Data Sources Used In Lbd Research?mentioning
confidence: 99%